การเมืองการปกครองของอังกฤษในสมัยราชวงศ์สจ๊วตและการสร้างประชาธิปไตยสมัยใหม่ในศตวรรษที่ 17: The Genesis of Modern Democracy during the Stuart Monarchy in the 17th Century - มานาดี ณัฐหทัย (Journal of Humanities and Social Sciences (HUSOKKU), 2025)
Abstract This study examines the politics and governance of Britain during The House of Stuart (1603–1714), with a particular focus on the conflict between the monarchy and Parliament, which played a crucial role in the transition from absolutism to modern democracy. This research employs a historical methodology, utilizing primary sources such as personal records, royal writings, and government documents from institutions including the House of Commons Information Office, National Archives, National Army Museum, The Royal Household, and UK Parliament. The 17th century marked a period of significant political transformations in England, including the Gunpowder Plot (1605), an attempted assassination of King James I and the bombing of Parliament as a reaction to religious persecution. The failure of this plot led to stricter measures against Catholics and reinforced Protestant dominance. The English Civil War (1642–1651) and the establishment of the Commonwealth of England (1649–1660) resulted in the execution of King Charles I and governance under Oliver Cromwell. However, Cromwell’s rule lacked stability, leading to the Restoration of the Stuart monarchy in 1660 under King Charles II. Despite the return of the monarchy, parliamentary influence continued to grow, particularly during the reign of King James II, who sought to restore Catholic power and govern without parliamentary consent. Public dissatisfaction and parliamentary opposition culminated in the Glorious Revolution (1688), which deposed James II and established William III and Mary II as joint monarchs. The enactment of the Bill of Rights (1689) firmly established parliamentary supremacy and laid the foundation for England’s transition to a constitutional monarchy.